Is There a Wage Premium for Returning Irish Migrants? - Philip J. O'Connell; Alan Barrett (Institute for the Study of Labor (IZA), 2000)
Higher rates of economic growth in recent years have led Ireland from being a country characterised by emigration to one where population inflows have become an important issue. This paper contains an analysis of one element of the current inflow. Drawing on data collected in 1998 on over 800 Irish individuals who had graduated from Irish colleges in 1992, we compare the wages of returned migrants with the wages of those who stayed in Ireland. In a recent paper, it has been argued that returned migrants accumulate skills and competencies while away that are rewarded on return to the home country. We find support for this argument for men. On average, returning males earn 10 percent more than men who stayed in Ireland, controlling for a range of factors. However, men who say that they originally migrated for labour-related reasons earn 15 percent more. No wage premium is found for female returning migrants relative to female stayers.
Keywords: J61; 330; Return migration; Ireland; Migranten; Rückwanderung; Lohnniveau; Irland